Factors affecting male-to-female ratio at birth in frozen-thawed embryo transfer cycles: a large retrospective cohort study - Du, Tong; Xie, Qin; Ye, Jing; Wang, Xindi; Qiu, Jiaxin; Yan, Zheng; Zhang, Suqun; Zhao, Dong; Lin, Jiaying; Li, Bin (Frontiers in Endocrinology, 2023)
Background ICSI (intracytoplasmic sperm injection) leads to a reduced male-to-female ratio at birth, whereas blastocyst transfer results in an increased male-to-female ratio. However, limited knowledge exists regarding the impact of these factors on the live birth rate for each gender. This study aimed to investigate the influence of patient characteristics and treatment parameters on the live birth rate for each gender, as well as the ultimate male-to-female ratio at birth in frozen-thawed embryo transfer (FET) cycles. Method This retrospective cohort study involved a total of 28,376 FET cycles and 9,217 subsequent deliveries, spanning from January 2003 to December 2015. The study consisted of two parts. First, logistic regression models were constructed to determine the factors influencing the male-to-female ratio among babies born after FET. Second, we aimed to investigate the mechanisms underlying this sex ratio imbalance by analyzing data from all transfer cycles. Generalized estimated equations were employed to assess the impact of risk factors on rates of male and female live births separately. Results ICSI resulted in a lower proportion of male offspring compared to in vitro fertilization (IVF) (50.1% vs. 53.7%, aOR: 0.87, 95% CI: 0.80-0.96). Conversely, blastocyst transfer yielded a higher proportion of male offspring than cleavage-stage embryo transfer (58.7% vs. 51.6%, aOR: 1.32, 95% CI: 1.17-1.48). Analysis of all cycles indicated that ICSI resulted in a reduced likelihood of male live birth in comparison to IVF (19.8% vs. 21.6%, aOR: 0.90, 95% CI: 0.83-0.97). However, the transfer of blastocysts rather than cleavage-stage embryos not only increased the chance of male live birth (26.9% vs. 20.2%, aOR: 1.70, 95% CI:1.56-1.85) but also facilitated female live birth (20.3% vs. 19.3%, aOR: 1.26, 95% CI: 1.15-1.39). Conclusion ICSI was associated with a reduction in the male-to-female sex ratio and a lower rate of male live births, while blastocyst transfer was associated with an increased male-to-female sex ratio at birth and a higher rate of male live births.